Corneal higher-order aberrations as key predictive indicators of axial elongation in myopic children with orthokeratology: a single-center prospective cohort study - Ju Zhang; Xiaoliang Zhang; Ranyi Ding; Yanan Ji; Zhe Zhu; Qingdong Bao; Ting Wang; Weiyun Shi (Scientific Reports)
Abstract This prospective study aimed to investigate changes in corneal higher-order aberrations (HOAs) in myopic children using orthokeratology (ortho-k) lenses and their relationship with myopia progression. A total of 112 children aged 8–13 years were divided into group A (axial elongation ≤ 0.1 mm/y with ortho-k) and group B (axial elongation > 0.1 mm/y with ortho-k). At baseline, 1, 6, and 12 months following the initiation of lens wear, HOAs and corneal peripheral defocus were evaluated. Ninety-three patients completed the 1-year follow-up. The mean axial elongation was − 0.07 ± 0.15 mm/y in group A, versus 0.32 ± 0.17 mm/y in group B. No statistical differences were observed in HOAs and corneal peripheral defocus at 1, 6, and 12 months (F = 0.653, 0.878; P > 0.05). Multivariate linear regression showed axial elongation was negatively correlated with ∆HOAs, peripheral defocus, and ∆horizontal coma (standardized beta=-0.331, -0.318, -0.209; P = 0.006, 0.001, 0.010, respectively) and positively correlated with the treatment zone diameter (standardized beta = 0.261, P = 0.003). Multivariate logistic regression identified ∆HOAs, peripheral defocus, ∆horizontal coma, and treatment zone as key factors distinguishing group A from group B (OR = 0.009, 0.455, 0.123, 12.172; P = 0.036, 0.003, 0.032, 0.019, respectively). The ROC curve for ∆HOAs had an area of 0.803 with a cut-off value of 0.834 μm. The ∆HOAs were more effective independent predictors of axial elongation than corneal peripheral defocus in children using ortho-k lenses. The ∆HOAs greater than 0.834 μm may lead to axial elongation ≤ 0.1 mm/y. These findings can be beneficial to fitting and optimizing ortho-k lenses.